Some Remarks concerning the Expressivity of the Romanian Language - Voicu-Stanciu, Mihaela (Acta Universitatis Danubius. Communicatio, 2023)
In this article, I aim at presenting some relevant opinions regarding the concept of expressiveness from a stylistic point of view. Most of these opinions and ideas, taken here into consideration, belong to Romanian linguists or literary critics (such as Iorgu Iordan, Tudor Vianu, Dumitru Caracostea, Ion Coteanu and others), even when they try to interprete or to adapt (according to their own perspective) the conceptions of some important foreign linguists (such as Ch. Bally, R. Jakobson et alii). At the same time, mention must be made that a goal of this article is to render the respective Romanian ideas in connection to the expressive (linguistic) resources of the Romanian language itself.